2022
DOI: 10.7861/clinmed.2021-0600
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced coronary artery disease: a difficult clinical conundrum

Abstract: Accelerated coronary artery disease seen following radiation exposure is termed 'radiation-induced coronary artery disease' (RICAD) and results from both the direct and indirect effects of radiation exposure. Long-term data are available from survivors of nuclear explosions and accidents, nuclear workers as well as from radiotherapy patients. The last group is, by far, the biggest cause of RICAD presentation.The incidence of RICAD continues to increase as cancer survival rates improve and it is now the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Firstly, the cardiovascular risk factors must be identified since they are important contributors to the progression of atherosclerosis and the onset of acute coronary events. This is of major concern since studies of cancer survivors beyond 5 years post-diagnosis have demonstrated a 1.7- to 18.5-times increased incidence of cardiovascular risk factors including hypertension, diabetes mellitus, and dyslipidemia when compared with age-matched counterparts without a history of cancer [ 193 ]. Lifestyle changes such as smoking cessation and exercise and pharmacological therapies are similar to those in the general population although some authors have proposed stricter targets [ 79 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the cardiovascular risk factors must be identified since they are important contributors to the progression of atherosclerosis and the onset of acute coronary events. This is of major concern since studies of cancer survivors beyond 5 years post-diagnosis have demonstrated a 1.7- to 18.5-times increased incidence of cardiovascular risk factors including hypertension, diabetes mellitus, and dyslipidemia when compared with age-matched counterparts without a history of cancer [ 193 ]. Lifestyle changes such as smoking cessation and exercise and pharmacological therapies are similar to those in the general population although some authors have proposed stricter targets [ 79 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Active malignancy, which is defined as a diagnosis within the previous 12 months or ongoing active cancer therapy including surgery, chemotherapy, or radiotherapy, is considered one of the major criteria for high bleeding risk, as outlined by the Academic Research Consortium for High Bleeding Risk [15,16]. In a study by Raposeiras-Roubin et al [17], 1 in 13 post-discharge bleeding events noted in ACS patients was associated with new cancer (positive predictive value for cancer diagnosis of post-discharge bleeding = 7.7%), affecting mainly the gastrointestinal, genitourinary, and bronchopulmonary systems [18]. Moreover, radiation-induced CAD (RICAD), which results from both direct and indirect effects of radiation exposure, is the second most frequent cause of morbidity and mortality among patients exposed to radiotherapy for breast cancer and Hodgkin lymphoma [16].…”
Section: Challenges Of Treating Acs In Cancer Patientsmentioning
confidence: 99%
“… 1 Clinical features can be occult and may only develop with severe disease. 2 Whilst technological advancement in radiotherapy delivery and cardiac shielding has mitigated toxicity, there is a growing cohort of cancer survivors who will require vigilant, lifelong cardiac follow-up.…”
Section: Case Reportmentioning
confidence: 99%